Student intention on entrepreneurship at University Malaysia Kelantan - Kavitha Kumari A/P Ramamoorthy (2012)
In recent year the intention towards entrepreneurship has been increased especially among the graduates of the tertiary education. Entrepreneurial intentions would be the first step in the evolving of venture creation. The student intention on entrepreneurship has been influence by several factors. This study is aim to determine the student intention on entrepreneurship at University Malaysia Kelantan and which factors influence in develops student intention on entrepreneurship. Factors examined include entrepreneurship education, self-efficacy, entrepreneurial competencies and demographic details ranging from sex, age, race, faculty and year of study. A total of 150 questionnaires were distributed to the student of University Malaysia Kelantan. Data collected was analyzed using Statistical Package for Social Science (SPSS) version 18.0. Finding shows that student intention on entrepreneurship is driven by entrepreneurship education, self-efficacy and entrepreneurial competencies. Discussion on findings, conclusion and limitations of study are also included in the report.